(untitled) - Lutterschmidt, William I. (NewYork, 2008)
This stand-alone laboratory text has been developed as an introduction to fundamental concepts in physiology. The text has been designed to emphasize an experimental approach to teaching physiology and is therefore designed for a particular type of student and curriculum. Many of the exercises will help students develop their clinical knowledge of physiology, plus help them gain an appreciation for the clinical techniques as would be needed by students studying nursing, physical therapy, and other health-oriented fields
Keywords: Human physiology,Sinh lý người; Laboratory manuals,Sổ tay phòng thí nghiệm